Wartime paediatric extremity injuries: experience from the Kabul International Airport Combat support hospital. Issue 3 (May 2015) - Mathieu, Laurent; Bertani, Antoine; Rongiéras, Frédéric; Chaudier, Philippe; Mary, Pierre; Versier, Gilbert
Abstract : Since the beginning of Operation Enduring Freedom, management of Afghan military or civilian casualties including children is a priority of the battlefield medical support. The aim of this study is to describe the features of paediatric wartime extremities injuries and to analyse their management in the Kabul International Airport Combat Support Hospital. A retrospective review was carried out using the French surgical database OPEX (Service de Santé des Armées) from June 2009 to January 2013. Paediatric patients were defined as those younger than 16 years old. Of the 220 injured children operated on, 155 (70%) sustained an extremity injury and were included. The mean age of the children was 9.1±3.8 years. Among these children, 77 sustained combat-related injuries (CRIs) and 78 sustained noncombat-related injuries (NCRIs), with a total of 212 extremities injuries analysed. All CRIs were open injuries, whereas NCRIs were dominated by blunt injuries. Multiple extremities injuries and associated injuries were significantly more frequent in children with CRIs, whose median Injury Severity Score was higher than those with NCRIs. Debridement and irrigation was significantly predominant in the CRIs group, as well as internal fracture fixation in the NCRIs group. There were four deaths, yielding a global mortality rate of 2.6%. This study is the first to analyse specifically paediatric extremities trauma and their management at level 3 of battlefield medical facilities in recent conflicts. Except for severe burns and polytrauma, treatment of paediatric extremities injuries can be readily performed in Combat Support Hospitals by orthopaedic surgeons trained in paediatric trauma.